Lenin e la Rivoluzione - Fresu, Gianni (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2019)
The centenary of the October Revolution was spent in a cultural and political climate that was certainly not favorable to free intellectual confrontation and very little available to evaluate reasons and inheritance of an event that, whatever our subjective judgment may be, represents a radical change of pace in the history of humanity which cannot be ignored. This has conditioned any analytical attempt to deal in a "disinterested" manner with the biography of the Russian revolutionary, preventing the evaluation of his entire intellectual and political production without prejudice. However, if Lenin is framed as an example of historiographic teratology, it becomes difficult to evaluate his role in a scientific perspective and it becomes impossible to understand the features of a theory that, apart from Russian events, has opened to Marxism the doors of distant and peripheral continents, making possible revolutionary processes not even imaginable according to the canons of the old Western Marxism, linked to the paradigms of determinist positivism. Historical Materialism; Dialectics; Revolution.